Phase Formation Processes in Natural Magnesium Silicates of Various Structures by Ammonium Fluoride Treatment; Refractories and Industrial Ceramics; Vol. 61, iss. 2 - Sharafeev Sh. M. Sharif Mnirovich (2020, 2020)
Title screen